Accounting in the Development of the Digital Economy - Kuz, Vasyl ("Artifex" University of Bucharest, 2021)
In the conditions of development of digital economy and use of information and communication technologies in accounting process the basic parameters of functioning of system of accounting change. The purpose of accounting does not lose its traditional meaning, but the requirements for the quality of accounting information increase, and due to the increase in the number of objects of accounting and information requests of users on the content and form of presentation, the studied information system should perform additional consolidation, creative and predictive functions. The system of methods of processing and disclosure of credentials is significantly expanded. The accounting system in the digital economy should provide real-time accounting data processing, electronic data exchange, application of software standards for reporting data, the use of «cloud technology» and artificial intelligence, econometric methods and methods of mathematical modeling to solve accounting and management tasks. With the help of information and communication technologies it is possible to ensure optimal disclosure of information in accordance with the information requests of users. The development of accounting in the context of digitalization of economic processes increases the list of necessary professional competencies of accountants aimed at studying the content and features of the use of information and communication technologies in economic processes.
Keywords: digital economy; accounting; information and communication technologies; purpose, tasks, functions, objects and methods of accounting; information disclosure; professional competencies of accountants